Efeito de maturadores sobre a germinação e crescimento inicial de corda-de-viola - Cesarin, Anne Elise [UNESP] (2014)
The morning-glory development on sugarcane crop occurs in the phase of higher growth of sugarcane. After this stage, the sugarcane stops increasing its biomass and begins the maturation stage. During this stage, the morning-glory plants are in different development stages and it usually coincide with the time of ripeners application on sugarcane.The main of this research was to evaluate the effect of ripeners used in sugarcane crop on the seeds germination, seedling development and abscission of the reproductive structures of Ipomoea hederifolia. The experiment was carried out in UNESP/FCAV- Jaboticabal, SP, Brazil. It was apllied five ripeners (ethyl-trinexapac, glyphosate, fluazifop-p-butyl, sulfometuron-metil and ethephon) and one control (without ripeners) during the reproductive period of I.hederifolia. After ripeners application, were counted abscised reproductive structures to determine the percentage of abscission of reproductive structures. The seeds of each phonological stage were collected when it reached the point of physiological maturity and it was disposed to germinate in Petri dishes to evaluate the seed germination, germination time, germination rate, initial growth and dry mass weight. Ethyl-trinexapac, glyphosate e fluazifop-p-butyl application when plants are with open flowers can reduce seed viability. Glyphosate showed the smallest length value and it can affect seedling growth. Glyphosate and ethephon caused the highest percentages of abscission of I. hederifolia reproductive structures and, it can contribute to reducing the seeds inflow to the soils